Local Specialty Product Innovation of Tilapia Fish Nugget “Spirunila” through the Empowerment of Karangtaruna Pemuda Mudi Gabahan (PMG) and Persons with Disabilities in Mulur Village - Agung Setyarini; Sari Widati; Salsabila Amalia Putri Bumi; Fandi Galang Wicaksana; Sangga Rizki Ramadhan; Annisa Nur Safitri (LP2M of Institute for Research and Community Services - UIN Walisongo, 2025)
This community service program responds to the underutilization of tilapia production in Mulur Village, Sukoharjo, where limited product diversification constrains economic growth. The program introduced Spirunila, a fortified tilapia-based product, while empowering the PMG Youth Organization and persons with disabilities through an Inclusive Joint Business Group (KUBA). The Participatory Learning System (PALS) was implemented to deliver capacity-building activities in production technology, entrepreneurship, and digital marketing. Program effectiveness was evaluated using pre- and post-test questionnaires on seven indicators, which were analyzed using a Paired Sample t-Test, N-Gain Score, and Cohen’s d. The results showed statistically significant improvements (p < 0.001), high learning gains (N-Gain category: High), and substantial effect sizes (d > 1.97), demonstrating strong behavioral and capability transformation among partners. Institutional strengthening ensures sustainability through shared production governance and digital market expansion. The findings confirm that inclusive innovation in community-based fish processing can enhance rural economic diversification and reinforce village tourism competitiveness.